Fire and Invasive Plant Interactions - Deb Stone; Michael Andreu (EDIS)
Prescribed fire and invasive species are two common land management concerns in Florida; therefore it is important that land managers have a solid understanding of their interactions and how they affect the surrounding ecosystems. These interactions can be roughly categorized into two groups: the effects of the invasive plant on the fire regime and the impacts of fire on the invasive plant or other flora. For this review we chose four invasive species in the southeastern United States that cover a range of interactions with fire: Cogon grass (Imperata cylindrica), Chinese tallow (Triadica sebifera), old world climbing fern (Lygodium microphyllum), and Japanese climbing fern (L. japonicum). This publication details basic information on each species, what is known about how it interacts with fire, and synthesizes this knowledge into concrete management recommendations.